The Study of Processes with Verbs of Movement in Chanka Quechua - Ascencio Huaccho, Mery Eli (2021)
In this paper, the processes expressed with verbs of movement in Chanka Quechua, from the Ayacucho area, are briefly presented. Since Quechua is an agglutinative language, the aim of this paper is to analyze the function of suffixes from the semantic point of view. For this purpose, our theoretical framework is based on the contribution of cognitive semantics and on the relationship between semantics and grammar proposed by Moreno Cabrera (2003). The results of this work aim to classify and determine how the suffixes -man, -manta, -kama and -ta act in sentence constructions of movement.